(-)-Baclofen-induced and constitutively active inwardly rectifying potassium conductances in cultured rat midbrain neurons - O'Callaghan, John F. X.; Jarolimek, Wolfgang; Lewen, Andrea; Misgeld, Ulrich (Pflügers Archiv, 1996)
Biophysical and pharmacological properties, and development of the (-)-baclofen-induced potassium (KBac) conductance and the constitutively active inwardly rectifying potassium (KIR) conductance were characterised using the patch-clamp technique in cultured embryonic rat midbrain neurons. KBac conductance was induced by (-)-baclofen acting on γ-aminobutyric acid B (GABAB) receptors, and displayed a high degree of selectivity for potassium ions, an approximate square-root dependence of conductance on extracellular potassium concentration and strongly voltage-dependent activation. Ba2+ blocked the conductance in a voltage-independent manner, whereas Cs+ produced a voltage-dependent block. In the same preparation, the KIR conductance displayed biophysical properties indistinguishable from those of the KBac conductance. Block of KIR currents by Ba2+ was voltage independent (KI, 4 μM), whereas Cs+ produced a voltage-dependent block (KI, 370 μM at -100 mV, equivalent valence, z′, 1.67). The KBac and KIR conductances additionally displayed a strikingly similar pattern of development in culture; the specific conductance (nS/pF) of both conductances increased two- to three-fold between the first and second week in vitro, and remained constant thereafter.